Investigation of Underwater Acoustic Modems: Architecture, Test Environment & Performance - Poncela-González, Javier (My University, 2016)
Underwater acoustic communication has emerged as one of the active research and development area. There are several design challenges which need to be carefully address including modem size, power consumption, interference, data rate and communication distance. In this paper the architecture, test environment and performance of underwater acoustic modems designed in the last five years have been investigated. The outcomes of the investigation would be highly valuable for researchers, designers, and developers of the domain.
Keywords: Acústica submarina; Modems; Modems underwater